Biomarkers in Non-Schistosomiasis-related squamous cell carcinoma of the urinary bladder: A review. (March 2019) - Maia, Manuel Caitano; Hansen, Aaron; Alves, Carolina; Salah, Samer
Graphical abstract: Abstract: Non-urothelial (NU) histologies represent less than 10% of bladder cancers, with squamous cell carcinoma (SCC) being the most common subtype (approximately 5%). Bladder SCCs are subdivided into Schistosoma-related or non-Schistosoma-related tumors, with the latter being the most frequent subtype in the western world. Typically, these patients have been excluded or under-represented in clinical trials and thus little is known about treatment efficacy in bladder SCC. To address this paucity of data, extrapolation from urothelial carcinoma (UC) trials can be performed but this approach has inherent limitations. In the era of precision medicine, efforts to characterize the genomic and molecular profiles of bladder tumors may yield evidence to support new targets for effective therapies. We reviewed the available data on biomarkers of bladder SCC and provide suggestions on how these may influence therapeutic testing and clinical trials in the future.